(3JWhjQ GdCOGA GdLeQcj hGJaGbjGJ efXeI GdJLGQI GdYGdejI (B:s (3CeKdI YQHjI eNJGQI (B/s ((3GdbGgQI(B: s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2006)
(3GdEOGQI GdLeQcjI, GdJMOjGJ GdbGFeI hYfGUQ GdJWhQ(B- (3GJaGbjGJ efXeI GdJLGQI GdYGdejI (B((3GdJbjje GdLeQcj hGdaMU bHd GdTMf(B) (3hOhQgG aj GdJWhjQ GdLeQcj(B- (3NHQGJ HYV GdOhd GdYQHjI aj JWhjQ GdEOGQI GdLeQcjI(B- (3GdNdGUI hGdJhUjGJ(B.s
Keywords: (3GdLeGQcs; (3efXeI GdJLGQI GdYGdejIs